Amyloid-β Impairs Dendritic Trafficking of Golgi-Like Organelles in the Early Phase Preceding Neurite Atrophy: Rescue by Mirtazapine - Fabbretti, Elsa; Antognolli, Giulia; Tongiorgi, Enrico (Frontiers in Molecular Neuroscience, 2021)
Neurite atrophy with loss of neuronal polarity is a pathological hallmark of Alzheimer’s disease (AD) and other neurological disorders. While there is substantial agreement that disruption of intracellular vesicle trafficking is associated with axonal pathology in AD, comparatively less is known regarding its role in dendritic atrophy. This is a significant gap of knowledge because, unlike axons, dendrites are endowed with the complete endomembrane system comprising endoplasmic reticulum (ER), ER–Golgi intermediate compartment (ERGIC), Golgi apparatus, post-Golgi vesicles, and a recycling-degradative route. In this study, using live-imaging of pGOLT-expressing vesicles, indicative of Golgi outposts and satellites, we investigate how amyloid-β (Aβ) oligomers affect the trafficking of Golgi-like organelles in the different dendritic compartments of cultured rat hippocampal neurons. We found that short-term (4 h) treatment with Aβ led to a decrease in anterograde trafficking of Golgi vesicles in dendrites of both resting and stimulated (with 50 mM KCl) neurons. We also characterized the ability of mirtazapine, a noradrenergic and specific serotonergic tetracyclic antidepressant (NaSSA), to rescue Golgi dynamics in dendrites. Mirtazapine treatment (10 μM) increased the number and both anterograde and retrograde motility, reducing the percentage of static Golgi vesicles. Finally, mirtazapine reverted the neurite atrophy induced by 24 h treatment with Aβ oligomers, suggesting that this drug is able to counteract the effects of Aβ by improving the dendritic trafficking of Golgi-related vesicles.